Antibacterial Potential of Ethanol Extract Cream of Kersen Leaves (muntingia Calabura L) Against Pseudomonas Aeruginosa - Muhammad Nurul Fadel; Emma Jayanti Besan; Muhammad Ridwanto (Indonesian Journal of Global Health Research, 2025)
Bacterial infections remain a substantial health concern. Several resistant microorganisms can induce bacterial infections, including Pseudomonas aeruginosa. Some research indicate that Kersen leaves (Muntingia calabura L), due to its flavonoids, tannins, and saponins that have undergone clinical testing, possess antibacterial characteristics. This study seeks to evaluate the antibacterial efficacy of a 96% ethanol extract cream derived from Kersen leaves (Muntingia calabura L) against the proliferation of Pseudomonas aeruginosa bacteria. The research performed was experimental in a laboratory setting. The procedure for evaluating antibacterial efficacy via the disc diffusion method utilising formulations of 0%, 5%, 10%, 15%, and gentamicin. The technique of data analysis employing One Way ANOVA to discover differences in data. The antibacterial activity of the cream against Pseudomonas aeruginosa was tested, yielding a 5% inhibition of 17.33 mm (strong category), 10% inhibition of 19.00 mm (strong category), and 15% inhibition of 22.66 mm (very strong category). The research concludes that a 96% ethanol extract cream of Kersen leaves (Muntingia calabura L) possesses the potential to suppress the growth of Pseudomonas aeruginosa bacteria.